ChemInform Abstract: An Efficient One‐Pot, Regio‐ and Stereoselective Synthesis of Novel Pentacyclic‐Fused Pyrano[3, 2‐c]chromenone or Quinolinone Benzosultone Derivatives in Water. Issue 42 (1st October 2013) - Ghandi, Mehdi; Nazeri, Mohammad Taghi; Kubicki, Maciej
Abstract Hydroxybenzaldehydes react with phenylethenesulfonyl chloride and hydroxyquinolines or hydroxycoumarins via an O‐sulfonylation/Knoevenagel condensation/hetero‐Diels‐Alder reaction cascade.